(untitled) (Journal Of Educational and Psychological Researches, 2018)
The current research attempts to examine the relationship between social-psychological conflict and their relation to family upbringing approaches among the adolescents of intermediate stage according to sex and economical level. To do this, the researcher prepared a questionnaire to measure social-psychological conflict that consisted of (32) item divided on four dimensions, and also she prepared a questionnaire to measure family upbringing approaches which composed of (28) item divided on four dimensions. The sample was (260) male and female student from intermediate stage chosen randomly. The results revealed that there were significant differences between social-psychological conflict which went to male, there was a negative correlation between democratic approach and social-psychological conflict, there was a positive correlation among each of excessive caring, carelessness, domination and social-psychological conflict, there were no significant differences between male and female based on family upbringing approaches and finally, the result showed that the economical level had serious influence on social-psychological conflict in which decreasing of income level means increasing of social-psychological conflict and vice versa.